IMPLEMENTASI UNDANG-UNDANG NOMOR 20 TAHUN 2008 TENTANG USAHA MIKRO KECIL DAN MENENGAH TERHADAP PENGEMBANGAN USAHA ANYAMAN RUMBAI DI DESA SIDANG MAS BANYUASIN III KABUPATEN BANYUASIN - Haryani, Deffi (STIA SATYA NEGARA PALEMBANG, 2022)
This research is motivated by the fact that in its implementation it is in accordance with applicable regulations, namely the Implementation of Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises (MSMEs) on the Development of Tassel Weaving Business in the Village of Mas Banyuasin III, Banyuasin Regency. MSMEs are business activities carried out by individuals or privately owned business entities with the aim of growing and developing their businesses in the context of building a national economy based on just economic democracy. This study uses qualitative research methods, data collection techniques using observation, interviews, documentation and literature study. The findings of this study in the Village of Session Mas, Banyuasin III Regency in carrying out six implementation indicators, namely the interests fulfilled by the policy, the type of benefits generated, the desired degree of change, the position of policy makers, program implementers, and resources deployed. Based on the results of research and discussion of the findings of researchers in the field regarding the implementation of Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises on the Development of Tassel Weaving Business in the Village of Session Mas, Banyuasin III, Banyuasin Regency has been going well, with the support of the village officials of the Session Mas towards the tassel craftsman community who provides training, and increases the knowledge of the craftsmen, making the craftsmen in the village of Session Mas even more creative and can make their tassel craft business more advanced. Keywords: Implementation, Micro, Small and Medium Enterprises (MSMEs)